Analisis Strategi Peningkatan Daya Saing Pengrajin Kain Tenun Khas Pagatan Kabupaten Tanah Bumbu - Noor Vania Ananda; Siti Siti Mutmainah Zulfaridatulyaqin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
Tanah Bumbu regency has a group of home industries that produce pagatan woven fabrics. This fabric is a traditional cloth typical of the people of Tanah Bumbu Regency, South Kalimantan. The great potential to be able to develop pagatan weaving business to stay afloat and develop is the necessity to innovate the products produced. Pagatan woven fabric entrepreneurs are required to be able to utilize internal and external environmental conditions in developing their business, one of the efforts to facilitate in utilizing these conditions is to apply an environmental analysis that is SWOT analysis (Strength, Weaknesses, Opportunities, Treats). This research uses a type of quantitative research, the location of research conducted in Kusan Hilir Subdistrict. Research data source is primary data and data analysis used is descriptive analysis technique and SWOT analysis. The results showed the strategy used to improve the competitiveness of woven fabric typical pagatan Tanah Bumbu district is a strategy that is in quadrant II, S-T strategy (Strength-Treats) strategy that uses force to overcome threats.